UPACARA & UPAKARA HINDU: PERANAN TOUR GUIDE DALAM PENGEMBANGAN PARIWISATA SPIRITUAL DI BALI - Komang Trisna Dewi (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2020)
Bali is one of tourism destination which is famous in the world. In maintaining tourism sustainability in Bali, tourism development in Bali always based on “Tri Hita Karana” concept. This concept aimed to balance relation among human and God, human and human, and human and nature. Tourism sector in Bali has big influence for economic field of Balinese people. It is shown by the fact that the tourists’ interest in visiting historical, relaxation, meditation, and sacred places like temples. Foreign tourists, especially, often ask everything about how and why things, in this case rituals, happen and the essence and functions of all offerings made in relation to the ceremonies. From this, we as especially Hindus people that want to plunge into the world of tourism and or have been plunge into the world of tourism for more comprehend and learn about Banten or Upakara of Bali cultural generally in order to can be supply his/ her profession as a tour guide which is usually can give information that want to know by the tourists.   Keywords: Guide, tourism, upakara, banten, Spiritual Tour Guide